Equilibrium concentration of singlet oxygen in photoreaction of reaction center/carbon nanotube bionanocomposites. Issue 11 (7th July 2015) - Kinka, Anikó; Hajdu, Kata; Magyar, Melinda; Mucsi, László; Szabó, Tibor; Hernádi, Klára; Horváth, Endre; Magrez, Arnaud; Forró, László; Nagy, László
Abstract : The reaction center protein is the unit in the photosynthetic organisms in which the primary events of the photoelectric energy conversion take place during photosynthesis. When the photochemistry following the excitation of the reaction center by light is oversaturated there is a large probability to form reactive oxygen species (ROS, e.g., singlet oxygen ( 1 O2 )). Because the ROS components decrease the overall yield of the photochemical energy conversion there is a considerable effort in many laboratories to find conditions to reduce these harmful compounds. The aim of our work is to create a system by using carbon nanotubes (CNTs) and RCs for efficient light‐energy conversion. The role of the 1 O2 that destroys the RC structure is discussed. 1, 3‐Diphenylisobenzofuran was used to detect the concentration of the 1 O2 . Although, 1 O2 can be sensitized by CNTs in certain conditions, in our experiments the main sources of the 1 O2 are the RCs. The concentration of the 1 O2 in the equilibrium is determined by the forward sensitization and the backward deactivation processes of the components and functions of the CNT/RC composite.